INTERNSHIP AT A YOUNG AGE IN PROPHET MUHAMMAD'S BUSINESS MANAGEMENT PRACTICES - Ismail Ismail; Misrah Misrah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Islam always teaches how to practice appropriate business in Islamic business ethics, the behavior and character of the prophet who is always exemplified in business practice has always been the main basis for how to become a successful businessman, tough, responsible and willing to face various risks. This research is a descriptive qualitative research by revealing the nature, strategies and practices of the prophet's apprenticeship at a young age by identifying books and journals published on Google Schoolar. The results of this study reveal that the Prophet Muhammad was a successful businessman who could not be separated from his apprenticeship practice since he was 12 years old. His character and attitude have always been a role model for Muslims, especially in trading. If the business strategy carried out by the prophet and the characteristics inherent in the prophet become the basis for entrepreneurship, then there is no entrepreneur who acts unjustly towards his customers and there is great hope that all Muslim entrepreneurs will be successful in this world and the hereafter.